A Characterization of Self-Injurious Behavior among Turkish Adolescents. Issue 3 (December 2014) - Oktan, Vesile
The primary objective of the present research is to characterize the frequencies of self-injurious behaviors among Turkish adolescents and whether these vary by sex. The sample comprised 371 female and 309 male college students, randomly selected and studying in different colleges in Trabzon (Turkey). The Personal Information Form and the Inventory of Statements About Self-injury were administered. The most pervasive types of self-injurious behaviors reported were "preventing the healing of wounds (peeling the scabs), " "hitting oneself on a tough surface or self-hitting, " and "scratching letters, texts, shapes on skin." Sex differences in self-injurious behaviors were observed.